1991
DOI: 10.1002/pssa.2211270219
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower studies of lithium–zinc mixed ferrites

Abstract: A series of Li–Zn mixed ferrites with composition formula Li0.5–0.5xZnxFe2.5–0.5xO4 is prepared by the solid‐state reaction method. The variation of lattice parameter with composition is explained on the basis of tetrahedral ionic radius. Thermopower studies are undertaken over a temperature range 300 to 750 K by the differential method. From the Seebeck coefficient S, the values of charge carrier concentration n and mobility μe are computed. The values of n are found to decrease while those of μe are increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is noticed that the sign of the Seebeck coefficient for all samples is negative, indicting that the Cu-Zn ferrite behave as ntype semiconductor. The conduction mechanism in these ferrites is due to electrons [11], and many authors obtained similar results [12,13].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is noticed that the sign of the Seebeck coefficient for all samples is negative, indicting that the Cu-Zn ferrite behave as ntype semiconductor. The conduction mechanism in these ferrites is due to electrons [11], and many authors obtained similar results [12,13].…”
Section: Resultsmentioning
confidence: 89%
“…The conduction at lower temperature (below Curie temperature) is due to hopping of electrons [12] between Fe 3+ and Fe 2+ ions, whereas at higher temperature (above Curie temperature) due to polaron hopping [15]. [17] reported that the increase of Zn substitution tends to increase the Fe 2+ ions as demon-strated in above equation.…”
Section: Resultsmentioning
confidence: 90%
“…In the case of low mobility semiconductors like ferrites which have exceedingly narrow bands or localized levels, the charge carriers concentration per unit volume, n; can be written as [13] n ¼ N V…”
Section: The Thermoelectric Powermentioning
confidence: 99%
“…Due to the lattice vibrations, the ionic carriers are hopping from one site to another, thus leading to an exponential temperature dependence of the conduction. As a result, the mobility associated with carriers tends to increase exponentially with temperature according to the relation [21]:…”
Section: DC Conductivity and Mobilitymentioning
confidence: 99%
“…8 shows that s decreases with increasing of temperature for the investigated compositions of Cu-Si ferrite. According to quantum-mechanical tunneling model [21,28], the exponent s factor is temperature independent. The large overlapping polaron model [31] predicted that s decreases with increasing temperature up to certain temperature after which it begins to increase with further increase of temperature.…”
Section: Determination Of the Frequency Exponential Factormentioning
confidence: 99%